Experiential Meaning in Welcoming Speech of Asian Games 2018 in Indonesia - Chalimah, Chalimah (Journal of English Teaching and Learning Issues, 2018)
Assessing the experiential meaning in welcoming speech of Asian Games 2018 in Indonesia is essential to do to get the real face and character of Indonesian people, especially for the person who becomes the representative of all Indonesian people to speak in front of other Asian nations. The research contributes in the linguistic field because the data are investigated through systemic functional linguistics to be described further. The research gap is exploring the data found in the sport context in six kinds of processes. The data show that the speaker uses the material process in the first rank (45%) to show the activities done and the achievement, the second rank is for relational process (25%) that the speaker tends to give positive attribute and good identification for Indonesia and Asian nations. The last rank (15%) is for mental process and (15%) is for behavioral process which state about his feeling and his urge by using words about the intention to live in peace in Asia.